Analysis of changes to steel footbridge geometry within 25 years in sernice = Analiza zmian geometrii stalowej kładki dla pieszych w okresie 25 lat eksploatacji - Sztubecki, Jacek; Bujarkiewicz, Adam; Sobczak-Piąstka, Justyna; Janiak, Tomasz; Gajewski, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Identification of the technical condition of bridge structures should be supplemented by determination of structural displacements in relation to the adopted frame of reference and measurement of changes to the geometry of its individual elements. Of special value are the results of measurements of the same values obtained along an extended service life. They provide an opportunity to compare results, track down tendencies, and more quickly recognise signs of aggravating technical condition of structures.
Keywords: footbridges; steel footbridge; technical condition of structures; geometry of structures; kładki dla pieszych; klatka stalowa; stan techniczny konstrukcji; geometria konstrukcji